Pengaruh Literasi Keuangan Dan Parental Income Terhadap Perilaku Keuangan Mahasiswa : Studi Kasus Mahasiswa Manajemen Fakultas Ilmu Sosial dan Ilmu Politik Universitas Sembilanbelas November Kolaka - Patra Iriansyah; Niar Astaginy; Andry Stepahnie Titing (Institut Nalanda, 2023)
This research aims to determine: (1) the influence of financial literacy on the pocket money management behavior of management students at the faculty of social and political sciences, Sembilanbelas November Kolaka University (2) to determine the effect of parental income on the financial behavior of management students at the faculty of social and political sciences. Nineteen November Kolaka university politics. This research uses a quantitative method approach. Data collection in this research uses literature study, observation and distribution of questionnaires. The population of this research is management students class 2018-2021. Meanwhile, the sample for this research is 82 people. Testing this research instrument uses Validity Test and Reliability Test with SPSS 25.0. The data analysis technique used in this research is measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 3.0. Based on the research results, it is known that there is a positive and significant influence between the financial literacy variable on Financial Behavior as indicated by a t-statistic value of 4.631 with a P-Value of 0.000 and the Parental Income variable also has a positive and significant influence on Financial Behavior as indicated by the t-value statistics of 3.108 with a P-Value of 0.003.